Axonal response of mitochondria to demyelination and complex IV activity within demyelinated axons in experimental models of multiple sclerosis. Issue 1 (7th October 2022) - Licht‐Mayer, Simon; Campbell, Graham R.; Mehta, Arpan R.; McGill, Katie; Symonds, Alex; Al‐Azki, Sarah; Pryce, Gareth; Zandee, Stephanie; Zhao, Chao; Kipp, Markus; Smith, Kenneth J.; Baker, David; et al.
Abstract: Aims: Axonal injury in multiple sclerosis (MS) and experimental models is most frequently detected in acutely demyelinating lesions. We recently reported a compensatory neuronal response, where mitochondria move to the acutely demyelinated axon and increase the mitochondrial content following lysolecithin‐induced demyelination. We termed this homeostatic phenomenon, which is also evident in MS, the axonal response of mitochondria to demyelination (ARMD). The aim of this study is to determine whether ARMD is consistently evident in experimental demyelination and how its perturbation relates to axonal injury. Methods: In the present study, we assessed axonal mitochondrial content as well as axonal mitochondrial respiratory chain complex IV activity (cytochrome c oxidase or COX) of axons and related these to axonal injury in nine different experimental disease models. We used immunofluorescent histochemistry as well as sequential COX histochemistry followed by immunofluorescent labelling of mitochondria and axons. Results: We found ARMD a consistent and robust phenomenon in all experimental disease models. The increase in mitochondrial content within demyelinated axons, however, was not always accompanied by a proportionate increase in complex IV activity, particularly in highly inflammatory models such as experimental autoimmune encephalomyelitis (EAE). Axonal complex IV activity inversely correlated with the extent of axonal injury in experimental disease models. Conclusions: Our findings indicate that ARMD is a consistent and prominent feature and emphasise the importance of complex IV activity in the context of ARMD, especially in autoimmune inflammatory demyelination, paving the way for the development of novel neuroprotective therapies. Abstract : The mitochondrial content of demyelinated axons in animal models is significantly greater than myelinated axons, irrespective of the mode of experimental demyelination. The increased axonal mitochondrial content following demyelination is consistent with the recently reported axonal response of mitochondria to demyelination (ARMD), which can be enhanced to protect acutely demyelinated axons. In lysolecithin‐induced focal lesions, the increased mitochondrial content of demyelinated axons is reflected at the level of complex IV activity, whereas highly inflammatory models such as experimental autoimmune encephalomyelitis (EAE) show a relative lack of complex IV activity within demyelinated axons.